Fiqih Dakwah di Era disrupsi Digital Berbasis Moderasi Beragama - Khoirul Jazila; M Shollahudin Nur (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah IAI Uluwiyah Mojokerto, 2021)
this research is motivated by digging deeper and understand about the use and form of islamic da’wah that can be done through social media. . bearing in mind that praching, asking for good and forgiving evil is one of the strategic function of the human caliphate, with the complexity of the problems of human and the challenges of da’wah whih are increasingly board and complek, wichis marked the era of disruption. Therefore, improving the quality of Muballigh competencies must be carried out continuosly effectively by using social media. Therefore, understanding the fiqih of dakwah in the era of Disruption Is So importent. this study uses a qualitative methode with a phenomological approach. Related to the form of the method of social media da’wah can be described as follows: live broadcasts of lectures or recitations using the live features on social media. uploading da'wah video content conducting discussions or questions and answers on the direct (direct message) feature, uploading charity activities on photo, story and status features and making social media accounts private as a medium for preaching.